Analisis Kandungan Asam Fitat dan Tanin Nasi dari Beras Analog Berbasis Pangan Lokal sebagai Alternatif Pangan Fungsional: Analysis of Phytic Acid and Tannin Content of Local Food-Based Analogue Rice as an Alternative Functional Food - Rahmawati, Sri; Sabta Aji, Arif; Saloko, Satrijo; Aprilia, Veriani; S. Djidin, Radhiyya Tsabitah; Sailendra, Nova Veronika; Khoirunnisah, Frisqi Meilany (Amerta Nutrition, 2024)
Background: Analog rice is an alternative food diversification that has rice-like characteristics. Various food ingredients can be utilized to produce analog rice as functional and healthy foods. Objectives: This study aims to identify the effect of cooking techniques on the phytic acid and tannin content of analogous rice (made from sorghum, mocaf, glucomannan, and moringa flour) and C4 rice. Methods: This experimental research used RAL for two treatments, namely cooking rice with a steamer and a rice cooker. This research was conducted in October-November 2022 at the Chem-mix Pratama Laboratory. The sample used analog rice and C4 rice for phytic acid and tannin content analysis using the Infrared Spectrophotometry and UV-S Spectrophotometry methods. Results: The highest phytic acid content of analog rice cooked using a rice cooker and a steamer was 6.64 mg and 4.75 mg respectively. The highest average tannin content of analog rice cooked using a rice cooker and a steamer was 18.35 mg and 19.55 mg respectively. The highest phytic acid content of C4 rice cooked using a rice cooker and a steamer was 7.43 mg and 9.01 mg respectively. The tannin content of C4 rice cooked using e rice cooker and a steamer was 4.45 mg and 9.11 mg respectively. Conclusions: The phytic acid content of analog rice is lower than in C4 rice. The tannin content of analog rice is higher than C4 rice. Tannin content reduction in analog rice needs to be studied further.